Unique Properties of the Large Antigen of Hepatitis Delta Virus - Moraleda, Gloria (American Society for Microbiology, 1999)
The large form of the hepatitis delta virus (HDV) protein (L) can be isoprenylated near its C terminus, and this modification is considered essential for particle assembly. Using gel electrophoresis, we separated L into two species of similar mobilities. The slower species could be labeled by the incorporation of [(14)C]mevalonolactone and is interpreted to be isoprenylated L (L(i)). In serum particles, infected liver, transfected cells, and assembled particles, 25 to 85% of L was isoprenylated. Isoprenylation was also demonstrated by (14)C incorporation in vitro with a rabbit reticulocyte coupled transcription-translation system. However, the species obtained migrated even slower than that detected by labeling in vivo. Next, in studies of HDV particle assembly in the presence of the surface proteins of human hepatitis B virus, we observed the following. (i) Relative to L, L(i) was preferentially assembled into virus-like particles. (ii) L(i) could coassemble the unmodified L and the small delta protein, S. (iii) In contrast, a form of L with a deletion in the dimerization domain was both isoprenylated and assembled, but it could not support the coassembly of S. Finally, to test the expectation that the isoprenylation of L would increase its hydrophobicity, we applied a phase separation strategy based on micelle formation with the nonionic detergent Triton X-114. We showed the following. (i) The unique C-terminal 19 amino acids present on L relative to S caused a significant increase in the hydrophobicity. (ii) This increase was independent of isoprenylation. (iii) In contrast, other, artificial modifications at either the N or C terminus of S did not increase the hydrophobicity. (iv) The increased hydrophobicity was not sufficient for particle assembly; nevertheless, we speculate that it might facilitate virion assembly.